2021
DOI: 10.1126/scitranslmed.abe7099
|View full text |Cite
|
Sign up to set email alerts
|

Slow-wave sleep affects synucleinopathy and regulates proteostatic processes in mouse models of Parkinson’s disease

Abstract: Slow-wave modulation alters synuclein accumulation and regulates proteostatic pathways in Parkinson’s disease mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 99 publications
2
38
0
1
Order By: Relevance
“…20 In addition, experimental evidence using mouse models demonstrated that modulation of NREM qEEG activity may reduce α-synuclein aggregation. 21 As such, these studies may contextualise the finding that qEEG abnormalities in NREM sleep, rather than REM sleep, were associated with increased risk of incident PD in the present study. In the present spectral analysis, reduced α, β, and α/θ, were all found to be associated with increased PD risk (consistent with the characteristic slowing of EEG activity seen in PD during wakefulness).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…20 In addition, experimental evidence using mouse models demonstrated that modulation of NREM qEEG activity may reduce α-synuclein aggregation. 21 As such, these studies may contextualise the finding that qEEG abnormalities in NREM sleep, rather than REM sleep, were associated with increased risk of incident PD in the present study. In the present spectral analysis, reduced α, β, and α/θ, were all found to be associated with increased PD risk (consistent with the characteristic slowing of EEG activity seen in PD during wakefulness).…”
Section: Discussionsupporting
confidence: 51%
“…9 The absolute and relative power of the EEG in different frequency bands throughout the night were computed for REM and non-REM (NREM) separately. In this analysis, the qEEG measures of interest included the mean relative power for the following frequency bands: δ (0.1 -4 Hz), θ (4 -8 Hz), α (8 -12 Hz), β (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and γ (>30 Hz). In addition, using the absolute spectral power for α and θ, the α/θ power ratio (α/θ) -a synoptic index of EEG background slowing down -was calculated.…”
Section: Sleep Microstructure (Qeeg)mentioning
confidence: 99%
“…These associations are presumably attributable to the reduced efficacy of the glymphatic system as a result of sleep disturbance 30 , 31 , as the function of the glymphatic fluid is enhanced by sleep and regulated by circadian rhythms 32 . Previous studies revealed slow-wave sleep is the stage at which glymphatic drainage is enhanced 29 . A recent clinical study indicated that increased brain parenchyma mean water diffusivity was positively related to the proportion of total sleep time spent in the REM phase in healthy people 33 .…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Besides, other pathologies such as neuroinflammation 27 , reactive astroglioses 28 and sleep abnormalities 29 may also induce glymphatic dysfunction, and further animal and human studies are required to elucidate these processes.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Various animal models of PD, especially mouse models, are useful for examining the causal relationship between sleep and PD because the core mechanisms underlying the sleep-wake cycle and its regulation are shared between humans and mice ( 43 ). A recent study demonstrated in mouse models of PD that the administration of sodium oxybate enhanced SWS and reduced the accumulation of aggregated α-syn in the brain, although no major symptomatic effects were observed ( 44 ). Further investigations of the causal relationship between sleep disturbances and PD with a particular focus on PD symptoms and pathology are needed.…”
Section: Bidirectional Relationship Between Sleep and Pdmentioning
confidence: 99%